Noncommunicable Disease and Health Care-Seeking Behavior Among Urban Camp-Dwelling Syrian Refugees in Lebanon: A Preliminary Investigation (Mary Ann Liebert, 2021)
Purpose: Syrian refugees (SRs) in Lebanon are often relegated to informal camps with poor living conditions and substandard access to health care. This study examined the unique condition of urban camp-dwelling SRs in Lebanon. This population is rarely studied as they are marginalized and difficult to access. We sought to assess the prevalence of noncommunicable diseases (NCDs) and health care-seeking behaviors within this population. Methods: A randomized group of urban camp-dwelling SR participants completed a survey on disease burden, health care-seeking patterns, and attitudes toward care. A second group completed interviews regarding health care experiences. We present descriptive population and epidemiologic measures to quantify NCD burden and health care-seeking behaviors. Results: Of 101 participants, 39% reported arthritis, 25% skin infection, 24% high blood pressure, 16% chronic lung conditions, 16% eye disease, and 15% diabetes. Major themes from interviews with SRs included poor living conditions, high cost of health care services, and perceived discrimination by health care workers (HCWs). The major theme from interviews with HCWs was a perception that SRs received health care services similar to members of surrounding communities. Discussion: In this population, we found a higher prevalence of NCDs at younger ages than in the general SR population. We described perceived barriers to accessing health care, including the noteworthy finding of perceived discrimination by HCWs in a linguistically and culturally related host community. We discussed social determinants of health within the camp and refugees' ability to access health care services.